Using a vocabulary website to increase the vocabulary size of IT workers in Hanoi - Nguyễn, Thị Lương (2020)
This study investigated the potential effect of using a vocabulary website on increasing vocabulary size. The research aimed to figure out whether the use of vocabulary instruction website could help widen IT students’ vocabulary and to identify students’ attitude towards using the website instead of their traditional way. In order to accomplish these purposes, 15 students who are IT workers in one of my tutor classes in Hanoi were selected to participate in the study. All the students learned to take TOEIC exam to meet their company requirement which is 700 TOEIC and they came from the same linguistic background. To achieve this target in a short period of time, the students focus mainly on increasing the passive vocabulary. Three data collection instruments were employed, namely pre-test/post-tests and questionnaire. After one month, the post-test and a questionnaire were administered. The analysis of the data collected revealed that the students made encouraging progress in boosting vocabulary size by using the vocabulary website; besides, according to the result of the questionnaire these IT workers were more motivated to learn vocabulary than they usually do.